Construct validity and internal consistency of the revised Mental Health Literacy Scale in South African and Zambian contexts - Korhonen Joonas; Axelin Anna; Katajisto Jouko; Lahti Mari; MEGA consortium/Research Team (WILEY, 2026)
Aim: The aim of this study was to evaluate the construct validity and internal consistency of the revised Mental Health Literacy Scale (MHLS) in South Africa (SA) and Zambia.
Design: This cross-sectional study was conducted between October 2018 and December 2019.
Methods: The study population comprised PHC workers (n = 454) in five districts in SA and Zambia. Principal component analysis (PCA) was used to explore the construct validity, and Cronbach's alpha was applied to measure the internal consistency of the MHLS.
Results: Cronbach's alpha values for three attributes were below the appropriate level, but the value was strong (0.804) for the whole scale. The study found nine components explaining similar to 59% of the total variance of variables. All MHLS items loaded to main attributes based on the theory of MHL. The results stated that the revised version of the MHLS is a construct valid instrument with strong internal consistency.